2012
DOI: 10.1111/j.1464-410x.2012.11618.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal angiomyolipoma

Abstract: What ' s known on the subject? and What does the study add? Renal angiomyolipomas (AMLs) were fi rst described in 1900 by Grawitz when he published a description of a large renal tumour composed of fat, muscle and blood vessels. Over the subsequent 100 years a lot has been discovered about the AML of the kidney. Initially, it was thought to be a hamartoma, an abnormal proliferation of tissues that are normally present in the kidney. More recent studies and observations have led to these lesions being classed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
10

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 11 publications
0
26
0
10
Order By: Relevance
“…With improvement of cross sectional imaging and even in cases of low-fat tumors, AMLs can now be confidently diagnosed with an MRI specificity of up to 99% (52,53 (25)(26)(27)36). Literature comparing nephrectomy and NSS with SAE in the management of AMLs is limited (3,8,55,56) with medical and economic analyses favoring embolization in symptomatic renal AMLs or AMLs at risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…With improvement of cross sectional imaging and even in cases of low-fat tumors, AMLs can now be confidently diagnosed with an MRI specificity of up to 99% (52,53 (25)(26)(27)36). Literature comparing nephrectomy and NSS with SAE in the management of AMLs is limited (3,8,55,56) with medical and economic analyses favoring embolization in symptomatic renal AMLs or AMLs at risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…10 Even in cases of small or fat-poor angiomyolipomata, magnetic resonance imaging demonstrates a specificity of 99%. 11 Many centers now favor transarterial embolization of angiomyolipoma, and reserve surgery for patients with refractory symptoms, complex renal artery anatomy, failure of embolization, and rare cases of diagnostic uncertainty.…”
Section: Current Management Strategies Of Angiomyolipomamentioning
confidence: 99%
“…We would like to focus on the recommendations for the surveillance and management of renal lesions [6]. Although ultrasound and computed tomography (CT) are adequate for the detection of the adipose component of angiomyolipomas, fat-poor lesions can be missed [78,79]. It has been suggested that MRI is superior to ultrasound and CT, and represents the preferred evaluation modality for angiomyolipomas (especially fat-poor lesions) [15,80,81] in newly diagnosed patients, and for 1-to 3-yearly follow-up throughout their lifetime [5,6].…”
Section: Recommendations For the Surveillance Of Tsc Patientsmentioning
confidence: 99%